Effects of Ar–N2–O2 Microwave Plasma on Poly‐L‐Lactic Acid Thin Films Designed for Tissue Engineering. Issue 6 (27th March 2013) - Chichti, Emna; Henrion, Gerard; Cleymand, Franck; Jamshidian, Majid; Linder, Michel; Arab‐Tehrany, Elmira
Abstract Poly‐lactic acid (PLA) is the most used biopolymer in both biomedical and food packaging fields to replace petrochemical plastics. The surface properties of PLA thin films were studied before and after plasma treatment to enhance its wettability and its adhesive properties. Based on the experimental design, the most significant parameters of the plasma process were specified. The effect of the cold plasma treatment on the mechanical, topographic composition, thermal and barrier properties of the PLA was carried out using different Ar–N2–O2 gas mixture. Results show that the discharge gas can have a significant influence on the chemical composition and the wettability of the PLA surfaces. As the plasma processing is a surface treatment without affecting the bulk properties, it did not change the PLA properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>